A house for mouse - Shook, Babs.; Couri, Kathryn A. (Pleasantville, N.Y. : Reader's Digest Children's Books, 2000)
Several animals offer to let a little mouse live with them, but she keeps searching until she finds just the right home.
"Preschool-grade 1"--cover.
Accelerated Reader AR
Keywords: Mice -- Fiction; Animals -- Habitations -- Fiction; Stories in rhyme